2022
DOI: 10.1017/s2045796022000385
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequities in multimorbidity among people with psychosis: a retrospective cohort study

Abstract: Aims Research shows persistent ethnic inequities in mental health experiences and outcomes, with a higher incidence of illnesses among minoritised ethnic groups. People with psychosis have an increased risk of multiple long-term conditions (MLTC; multimorbidity). However, there is limited research regarding ethnic inequities in multimorbidity in people with psychosis. This study investigates ethnic inequities in physical health multimorbidity in a cohort of people with psychosis. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…44,179,181,185 Poorer health-related quality of life and self-rated health, both predictors of mortality, have been found in several minoritized ethnic groups. 173,174 Language barriers could account for some instances of poor care among immigrants, who may have difficulty making their needs known to providers; improving access to professional interpreters has the potential to improve clinical care in these cases. 186 The effect of racism and discrimination on multimorbidity appears to operate through, or in concert with, the biological and psychological factors discussed earlier.…”
Section: Therapeutic Advances In Psychopharmacologymentioning
confidence: 99%
“…44,179,181,185 Poorer health-related quality of life and self-rated health, both predictors of mortality, have been found in several minoritized ethnic groups. 173,174 Language barriers could account for some instances of poor care among immigrants, who may have difficulty making their needs known to providers; improving access to professional interpreters has the potential to improve clinical care in these cases. 186 The effect of racism and discrimination on multimorbidity appears to operate through, or in concert with, the biological and psychological factors discussed earlier.…”
Section: Therapeutic Advances In Psychopharmacologymentioning
confidence: 99%
“…Of the 42 full-text articles, 23 articles were excluded due to lack of relevant outcomes, not including analysis on the association between severe mental illness and physical multimorbidity, and mental health diagnoses were not obtained. This left 19 articles to be included in the systematic review 25–41…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis of ethnic inequalities in physical health MLTCs among people with psychosis living in the UK found that Black people were at higher risk of psychosis compared to white people (Fonseca de Freitas et al., 2022). The differences between our findings and those of Fonseca de Freitas and colleagues could be attributed to the fact that their study included people below 18 years (age range 13–65 years) and focused on people with a particular type of severe mental illness: psychosis.…”
Section: Discussionmentioning
confidence: 99%